Pentaho Reporting 3.5 for Java developers : create advanced reports, including cross tabs, sub-reports, and charts that connect to practically any data source using open source Pentaho Reporting - Gorman, Will (From technologies to solutions., 2009)
Create advanced reports, including cross tabs, sub-reports, and charts that connect to practically any data source using open source Pentaho Reporting.